Analisis Pelaksanaan Pembiayaan Multiguna Akad Murabahah PT Bank Sumut KCP Syariah Multatuli - Jamisah Ulfa; Nurul Inayah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Multipupose financing PT Bank Sumut KCPSy Multatuli is the provision of funds for various purposes that are consumptive/investmnet/working capital eith the principle of buying and selling (Murabahah) wichh is intended for employees of one agency that entered into an MOU with PT Bank Sumut UUS. The application of murabahah contracts in multifunctional finance is discussed in this article. This study uses a qualitative method with a descriptive approach, as well as transcripts of data from interviews and supporting materials related to the book in question. Based on the findings of this study, the process of implementing multipurpose financing for a murabaha contract includes the following steps: multipurpose financing application, MOU agreement, financing committee approval, customer account opening, contract signing, approval, and disbursement, all of which are completed individually and collectively. . This study was used by the Bank of North Sumatra KCP Syariah Multatuli.